Magnetic microcalorimeter with paramagnetic temperature sensors and integrated dc-SQUID readout for high-resolution x-ray emission spectroscopy - Krantz, Matthäus; Toschi, Francesco; Maier, Benedikt; Heine, Greta; Enss, Christian; Kempf, Sebastian (Applied physics letters, 2024)
We present two variants of a magnetic microcalorimeter with paramagnetic temperature sensors and integrated dc-superconducting quantum interference device readout for high-resolution x-ray emission spectroscopy. Each variant employs two overhanging gold absorbers with a sensitive area of 150 × 150 μm2 and a thickness of 3 μm, thus providing a thickness related quantum efficiency of >98% for photons up to 5 keV and >50% for photons up to 10 keV. The first variant operated nominally but suffered from Joule power dissipation of the Josephson junction shunt resistors, athermal phonon loss, and slew rate limitations of the overall setup. Overall, it only achieved an energy resolution of Δ E FWHM = 8.9   eV for 5.9 keV photons. In the second variant, we introduced an innovative tetrapod absorber geometry as well as a membrane technique for diverting dissipated heat away from the temperature sensors. When all mitigations are applied optimally, the second variant achieves an energy resolution of Δ E FWHM = 1.25 ( 18 )   eV for 5.9 keV photons and hence provides the present best energy resolving power E / Δ E FWHM among all existing energy-dispersive detectors for soft and tender x-rays.
Gesehen am 11.10.2024